Mucosal and Histologic Healing in Children With Inflammatory Bowel Disease Treated With Antitumor Necrosis Factor-Alpha. Issue 5 (May 2021) - Scarallo, Luca; Alvisi, Patrizia; Bolasco, Giulia; Di Toma, Michele; Lanari, Marcello; Cangiari, Alice; Paci, Monica; Naldini, Sara; Renzo, Sara; Barp, Jacopo; De Masi, Salvatore; Lionetti, Paolo
ABSTRACT: Objectives: Mucosal healing (MH) and histological healing (HH) have been recently proposed as a novel treatment target for inflammatory bowel disease (IBD). The aim of the present study was to evaluate real-life achievement of such outcomes in a cohort of pediatric patients with IBD treated with anti-TNF-alpha (ATA) agents. Methods: A retrospective analysis was performed on patients affected by IBD who received ATA and were followed up at two referral centers. Incidence and cumulative rates for MH and HH for each group were calculated. Results: Of 170 (105 Crohn's disease [CD] and 65 ulcerative colitis [UC]) patients, 78 with CD and 56 with UC underwent endoscopic re-assessment during the study period. MH was achieved by 32 CD (41%) and 30 UC (53.6%) patients; 26 CD (33.3%) and 22 UC (39.3%) patients achieved HH. MH incidence rate was 19.1/1000 and 47/1000 person-months, whereas HH incidence rate was 15.5/1000 and 34.7/1000 person-months for CD and UC, respectively. Remission at the end of induction was associated with higher MH and HH rates (HR: 2.43, P = 0.049 and HR: 2.94, P = 0.046, respectively) in CD. In UC, adalimumab was associated with lower MH and HH rates (HR: 0.16, P = 0.004 and HR: 0.07, P = 0.003). Conclusions: We reported a real-life experience arising from a large cohort of pediatric IBD who received ATA scheduled treatment. Less than half of patients with CD and only a little >50% of UC patients achieved MH. Microscopical inflammation was observed in 18.8% CD and 26.7% UC patients who achieved MH. Overall, MH and HH rates appear lower compared to previously published data. Abstract : Supplemental Digital Content is available in the text